Simian virus 40 DNA replication in vitro: identification of multiple stages of initiation. - Tsurimoto, T (1989)
A cell-free DNA replication system dependent upon five purified cellular proteins, one crude cellular fraction, and the simian virus 40 (SV40)-encoded large tumor antigen (T antigen) initiated and completed replication of plasmids containing the SV40 origin sequence. DNA synthesis initiated at or near the origin sequence after a time lag of approximately 10 min and then proceeded bidirectionally from the origin to yield covalently closed, monomer daughter molecules. The time lag could be completely eliminated by a preincubation of SV40 ori DNA in the presence of T antigen, a eucaryotic single-stranded DNA-binding protein (replication factor A [RF-A]), and topoisomerases I and II. In contrast, if T antigen and the template DNA were incubated alone, the time lag was only partially decreased. Kinetic analyses of origin recognition by T antigen, origin unwinding, and DNA synthesis suggest that the time lag in replication was due to the formation of a complex between T antigen and DNA called the T complex, followed by formation of a second complex called the unwound complex. Formation of the unwound complex required RF-A. When origin unwinding was coupled to DNA replication by the addition of a partially purified cellular fraction (IIA), DNA synthesis initiated at the ori sequence, but the template DNA was not completely replicated. Complete DNA replication in this system required the proliferating-cell nuclear antigen and another cellular replication factor, RF-C, during the elongation stage. In a less fractionated system, another cellular fraction, SSI, was previously shown to be necessary for reconstitution of DNA replication. The SSI fraction was required in the less purified system to antagonize the inhibitory action of another cellular protein(s). This inhibitor specifically blocked the earliest stage of DNA replication, but not the later stages. The implications of these results for the mechanisms of initiation and elongation of DNA replication are discussed.